1993
DOI: 10.1002/1097-0142(19931115)72:10<3029::aid-cncr2820721027>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein in testicular germ cell tumors and drug resistance: Clinical correlation

Abstract: Background. Metallothioneins (MT) are endogenous metalloproteins involved in the homeostasis of essential metals and detoxification of toxic metals. Some recent experimental studies suggested tumor resistance to cisdiamminedichloroplatin may be associated with overexpression of MT in the tumor. Methods. The presence of MT in 33 primary testicular germ cell tumor specimens was assessed immunohistochemically using a rabbit polyclonal rat liver MT antibody that cross‐reacted with human MT. The data were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…In stage IV melanoma patients, anticancer drugs, as well as irradiation therapy, are known to often show only a humbled rate of clinical responses. These therapeutic failures may partially be related to an enhanced MT overexpression in tumour cells, although the involvement of MT in conferring resistance to chemotherapeutics still remains under discussion (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Cherian et al, 2003). As a variety of endogenous factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stage IV melanoma patients, anticancer drugs, as well as irradiation therapy, are known to often show only a humbled rate of clinical responses. These therapeutic failures may partially be related to an enhanced MT overexpression in tumour cells, although the involvement of MT in conferring resistance to chemotherapeutics still remains under discussion (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Cherian et al, 2003). As a variety of endogenous factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, MT are involved in many physiological and pathophysiological processes such as the intracellular storage, transport and metabolism of heavy metal ions; they regulate essential trace metal homeostasis and play a protective role in heavy metal detoxification reactions (Miles et al, 2000;Simpkins, 2000). They can protect cells against UV-/ionic radiation (Hansen et al, 1997;Hanada et al, 1998;Reeve et al, 2000) as well as cytotoxic alkylating agents including chemotherapeutics (Chin et al, 1993;Hishikawa et al, 1997;Okazaki et al, 1998;Sunada et al, 2005), modulate oxygen free radicals and nitric oxide and inhibit apoptosis (Tsangaris and Tzortzatou-Stathopoulou, 1998). The synthesis of MT is induced by group II heavy metal ions as well as by endogenous factors such as glucocorticoids, cytokines (interleukin (IL)-1 or IL-6, interferon g (IFNg), tumour necrosis factor a (TNF-a)) or vitamin D 3 (Karin et al, 1985;Karasawa et al, 1987;Schroeder and Cousins, 1990;Sato and Sasaki, 1992;Nishimura et al, 2000).…”
mentioning
confidence: 99%
“…Tumour MT level also has been reported to correlate with resistance to anticancer reagents (Kelley et al, 1988;Kasahara et al, 1991;Chin et al, 1993;Kondo et al, 1995;Hishikawa et al, 1997). In oesophageal SCC, we already reported that MT protein expression might be a significant determinant of prognosis, in particular, associated with cisplatin resistance (Hishikawa et al, 1997).…”
mentioning
confidence: 84%
“…MTs appear to have a physiological role in the absorption, transport and metabolism of important trace metals, as well as a role in heavy metal detoxification. MTs have also been shown to affect the cellular sensitivity to cisplatinum (Bahnson et al, 1991; Kasahara et al, 1991;Chin et al, 1993;Kondo et al, 1995). No previous studies have reported on MT expression in OS.…”
mentioning
confidence: 99%